Adhesives derived from bagasse autohydrolysis lignin and waste phenolics for binding of wood products - Ysbrandy, R. E.(Robert Ernst) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1992.